2022
DOI: 10.1177/03000605211070766
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive meta-analysis of associations between temperament and character traits in Cloninger’s psychobiological theory and mental disorders

Abstract: Objective To explore the relationship between temperament and character traits in Cloninger’s psychobiological theory and mental disorders. Methods: A systematic literature search was conducted of five international databases for all articles published in English between January 1990 and April 2019 (PROSPERO-CRD42019133214). Owing to heterogeneity, pooled estimates of correlations for personality disorders and standardized mean differences for case–control studies related to other mental disorders were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
0
17
1
1
Order By: Relevance
“…Several review and meta-analytic studies have also pointed to the role of temperamental models in explaining the symptoms of NPDs [ 29 31 ]. The results of a comprehensive meta-analysis also showed that temperamental traits have a stronger relationship with NPDs than PDs [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several review and meta-analytic studies have also pointed to the role of temperamental models in explaining the symptoms of NPDs [ 29 31 ]. The results of a comprehensive meta-analysis also showed that temperamental traits have a stronger relationship with NPDs than PDs [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, those with higher effortful control might better cope with situations like dental treatment, and so be less likely to develop dental anxiety in which lack of control is a key phenomenon [6]. Previous publications have frequently reported an association between negative affect and more mental health symptoms, such as higher depression and general anxiety [29,30], which have also been associated with dental anxiety . Interestingly, general anxiety or depressive symptoms were not associated with dental anxiety when temperament dimensions were considered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The bivariate associations between dichotomized MDAS, temperament dimensions and education were assessed with Mann-Whitney U-test separately for women and men. The covariates were selected based on previous results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][29][30]. Finally, the associations between all temperament dimensions and dental anxiety at the same model (with cut-off for high dental anxiety (MDAS ≥ 19) in logistic regression) were modelled using linear and logistic regression analyses adjusted for general anxiety and depressive symptoms, education (as dummy variable in linear regression) and age, separately for women and men.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ofte skilles det mellom trekkimpulsivitet eller impulsiv personlighet og atferdsimpulsivitet (Sliedrecht et al, 2021;Um et al, 2018). Et eksempel på førstnevnte er Cloningers psykobiologiske teori, der impulsivitet er et aspekt ved temperamentstrekket nyhetssøking og disponerer for AUD (Komasi et al, 2022). I en nevropsykologisk sammenheng forstås impulsivitet som svikt i hemming mer enn ønske om nyhet og spenning.…”
Section: Kognitive Vanskerunclassified